Effectiveness of vestibular incision subperiosteal tunnel access (VISTA) technique with or without A-PRF in treatment of multiple adjacent gingival recession defects (MAGRD): A 12 months CBCT study - Prabhnoor Tuli; Abhay P. Kolte; Rajashri A. Kolte; Vrushali N. Lathiya; Vinisha A. Bajaj; Shahabe Saquib Abullais; Manea M. Alahmari (PLoS ONE, 2025)
Objectives In order to treat MAGRD in the maxillary anterior region, the VISTA approach was evaluated and compared with and without A-PRF. Materials and methods A split mouth RCT was designed with 216 MAGRD that were assigned to VISTA alone and VISTA with A-PRF. The complete root coverage (CRC) and gingival thickness (GT) were measured using CBCT at baseline and 12 months post-operatively, while the clinical parameters of probing depth (PD), clinical attachment level (CAL), width of keratinized gingival (WKG), gingival recession depth (GRD), and gingival recession width (GRW) were recorded at baseline, 6 months, and 12 months. Results From baseline to 12 months, there was a significant decrease in the mean values of GRD and GRW with an increase in WKG. CBCT scans showed a significant increase in GT mean values. According to these results, the Test group’s CRC was higher (95.92%) than the Control groups (85.02%). Conclusions In contrast to the Control group, the Test group demonstrated superior MAGRD resolution in achieving a decrease in GRD and GRW as well as a higher increase in WKG and GT. These findings resulted into a substantially more CRC for the Test group. Trial registration Registration no. CTRI/2022/09/045845. Registered on: 26/09/2022